Low level expression of glycine receptor beta subunit transgene is sufficient for phenotype correction in spastic mice - Hartenstein, Bettina; Schenkel, Johannes; Kuhse, Jochen; Besenbeck, Birgit; Kling, Claudia; Becker, Cord-Michael; Betz, Heinrich; Weiher, Hans (The EMBO journal, 1996)
Mutations in inhibitory glycine receptor (GlyR) subunit genes are associated with neuromotor diseases in man and mouse. To use the potential of the mouse mutants as animal models of human disease, we altered GlyR levels in mutant mice and studied their phenotype. A transgene coding for the beta subunit of the rat GlyR was introduced into the genetic background of the spa mutation, which is characterized by low endogenous expression levels of the beta subunit and a dramatic neuromotor phenotype. The resulting transgenic mice expressed the beta subunit mRNA at intermediate levels, and their phenotype was rescued. This provides formal proof for the casual relationship between GlyR beta gene mutation and motor disease, and indicates that a low level of beta gene expression (25% of normal) is sufficient for proper functioning of glycinergic synapses.
Gesehen am 07.10.2020